Marketing plan for workshop and accessories area of proóptica - Lopes, Joséphine Gaspar (2016)
Proóptica is a Portuguese company acting in the Optical Market as a distributor of international and national brands of this market. The company acts in four main areas: Frames and Sunglasses; Workshop and Accessories; Lenses and Design + Architecture. In April of 2014 I was invited by Professor Luís Justino to start an internship at this company. This was the year of turnover for Workshop and Accessories strategic business area that wanted to stop being a complementary area of frames and sunglasses, and start to be a more autonomous and present business area in the Portuguese market. Soon I realized that for this goal to be possible, a solid marketing plan needed to be constructed. Although, this seems to be a hard task, since the current optical market is changing every day and faces this business area as one of its last concerns in terms of needs and offer. Thus, this project proposes a possible market plan for this business area, mainly based on a deep external and internal analysis that observed the organization, the competition and the customer’s behaviour and needs. Through this analysis, marketing actions were proposed and carefully planned, following the marketing mix theory: product actions, price actions, place actions and promotion actions.